Composite negative electrode material, preparation method thereof, negative electrode material and lithium titanate battery
Patent Information
- Application Number
- CN202011536108.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2040-12-22
AI Technical Summary
[0004]本发明的主要目的在于提供一种复合负极材料及其制备方法、负极材料及钛酸锂电池,以解决现有技术中的钛酸锂电池的能量密度较低的问题
[0015] Applying the technical solution of this invention, titanium and niobium have similar atomic radii and similar chemical properties, while Ti 4 + /Ti 3+ The lithium intercalation/deintercalation plateau corresponding to the redox potential and niobium (Nb) 5+ /Nb 4+ The difference is not significant. The theoretical capacity of the titanium niobium oxide anode (TiNb2O7) is 387.6 mAh/g, and the lattice size before and after lithium insertion/extraction exhibits some expansion and contraction (<10%). Lithium titanate and titanium niobium oxide materials were combined to obtain Li... 4x Ti 4x+1 O 7+5x Nb 2-2x Composite anode materials can utilize the "zero strain" characteristic of lithium titanate to suppress the expansion and contraction of titanium niobium oxide anode materials. The high capacity of titanium niobium oxide anodes leads to a relative increase in energy density. The resulting composite anode material can effectively improve capacity or cycle performance, meeting diverse material requirements. In particular, this application, through the structural design of porous composite anode materials, shortens the diffusion path of lithium ions within the material, thus facilitating electrolyte penetration and improving the battery's rate performance. Overall, a lithium titanate battery with high energy density and high rate performance is achieved. Furthermore, the aforementioned raw materials are inexpensive and readily available, resulting in low cost.
Smart Images

Figure CN112652750B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a composite anode material and its preparation method, the anode material, and a lithium titanate battery. Background Technology
[0002] Spinel-type lithium titanate material (Li4Ti5O) 12 Li₄Ti₅O₃ possesses extremely high cycle life and safety characteristics, and is considered one of the most promising anode materials for lithium-ion batteries. Especially compared to graphite anodes, Li₄Ti₅O₃ exhibits superior performance. 12 It has a higher lithium intercalation potential (1.55V higher than that of metallic lithium), which effectively prevents the precipitation of metallic lithium and the formation of lithium dendrites. Li4Ti5O 12 and Lithium-intercalated Li7Ti5O 12 It possesses thermodynamic stability far exceeding that of graphite, making it less prone to thermal runaway in batteries and thus offering higher safety. Meanwhile, Li4Ti5O... 12 During lithium-ion insertion and extraction, the lattice parameters remain almost unchanged (the cell volume change is only 0.2%), and the crystal structure maintains high stability, making it a "zero-strain" material with excellent cycle stability. Furthermore, Li₄Ti₅O₂... 12 It also has excellent low-temperature performance, fast charging capability, and wide temperature range (operating temperature range -50 to 60℃).
[0003] But Li4Ti5O 12 Low energy density is one of the main drawbacks of lithium titanate batteries. Therefore, improving the energy density of lithium titanate batteries can effectively enhance the market competitiveness of lithium titanate materials. Summary of the Invention
[0004] The main objective of this invention is to provide a composite anode material and its preparation method, as well as the anode material and lithium titanate battery, to solve the problem of low energy density in existing lithium titanate batteries.
[0005] To achieve the above objectives, according to one aspect of the present invention, a composite anode material is provided, the composite anode material having the general structural formula Li. 4x Ti 4x+1 O 7+5x Nb 2-2x Where 0 < x < 1, the composite negative electrode material is a porous material.
[0006] Furthermore, the general structural formula of the above-mentioned composite anode material is xLi4Ti5O 12 ·(1-x)TiNb2O7, 0<x<1, preferably 0.2≤x≤0.4.
[0007] Furthermore, the composite negative electrode material is spherical in shape, preferably with a particle size of 10–34 μm and a specific surface area of 9–36 cm². 2 / g.
[0008] According to another aspect of the present invention, a method for preparing a composite anode material is provided, the method comprising: step S1, preparing Li4Ti5O 12 Nanoparticles and TiNb2O7 nanoparticles are pelletized to obtain microspheres; in step S2, the microspheres are calcined to obtain a composite anode material.
[0009] Furthermore, the calcination temperature is 500–800°C, and the preferred calcination time is 2–8 hours.
[0010] Furthermore, the above-mentioned pelletizing process includes: applying Li4Ti5O 12 Nanoparticles, TiNb2O7 nanoparticles, and a solvent are mixed to obtain a slurry. The slurry is then spray-balled to obtain microspheres. Preferably, the mixing speed is 300–1000 r / min, the mixing time is 1–3 h, the spray-balling temperature is 260–280 °C, the feed rate of the slurry during spray-balling is 1–30 mL / min, the solvent is selected from one or more of water, ethanol, and acetone, the solid content of the slurry is 15–60%, and Li4Ti5O7 is preferred. 12 The particle sizes of the nanoparticles and TiNb2O7 nanoparticles are independently 10–300 nm.
[0011] Furthermore, the above mixing includes: Li4Ti5O 12 The nanoparticles are first mixed with a first solvent to obtain a first slurry; the TiNb2O7 nanoparticles are second mixed with a second solvent to obtain a second slurry; the first slurry and the second slurry are third mixed to obtain a mixed slurry; preferably, the first solvent and the second solvent are each independently selected from any one or more of water, ethanol, and acetone; preferably, the solid content of the first slurry and the second slurry are each independently 15-60%; preferably, the stirring speed of the first mixing and the second mixing are each independently 1200-1800 r / min; preferably, the stirring speed of the third mixing is 1500-2400 r / min.
[0012] Furthermore, the above-mentioned Li4Ti5O 12 The molar ratio of TiNb2O7 to TiNb2O7 is 0.2–0.4:0.6–0.8.
[0013] According to another aspect of this application, a negative electrode material is provided, the negative electrode material comprising a composite material, the composite material being the aforementioned composite negative electrode material.
[0014] According to another aspect of this application, a lithium titanate battery is provided, including a positive electrode and a negative electrode, the negative electrode including a negative electrode material, the negative electrode material being the aforementioned negative electrode material.
[0015] Applying the technical solution of this invention, titanium and niobium have similar atomic radii and similar chemical properties, while Ti 4 + / Ti 3+ The lithium intercalation / deintercalation plateau corresponding to the redox potential and niobium (Nb) 5+ / Nb 4+ The difference is not significant. The theoretical capacity of the titanium niobium oxide anode (TiNb2O7) is 387.6 mAh / g, and the lattice size before and after lithium insertion / extraction exhibits some expansion and contraction (<10%). Lithium titanate and titanium niobium oxide materials were combined to obtain Li... 4x Ti 4x+1 O 7+5x Nb 2-2x Composite anode materials can utilize the "zero strain" characteristic of lithium titanate to suppress the expansion and contraction of titanium niobium oxide anode materials. The high capacity of titanium niobium oxide anodes leads to a relative increase in energy density. The resulting composite anode material can effectively improve capacity or cycle performance, meeting diverse material requirements. In particular, this application, through the structural design of porous composite anode materials, shortens the diffusion path of lithium ions within the material, thus facilitating electrolyte penetration and improving the battery's rate performance. Overall, a lithium titanate battery with high energy density and high rate performance is achieved. Furthermore, the aforementioned raw materials are inexpensive and readily available, resulting in low cost. Attached Figure Description
[0016] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0017] Figure 1 SEM images of a composite anode material improved according to Embodiment 1 of the present invention are shown;
[0018] Figure 2 It shows Figure 1 A magnified view of a portion of the SEM image shown; and
[0019] Figure 3 It shows Figure 2 A magnified view of a portion of the SEM image shown. Detailed Implementation
[0020] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0021] As analyzed in the background section, existing technologies suffer from low energy density in lithium titanate batteries. To address this issue, this invention provides a composite anode material, its preparation method, the anode material, and a lithium titanate battery.
[0022] In a typical embodiment of this application, a composite anode material is provided, the general structural formula of which is Li 4x Ti 4x+1 O 7+5x Nb 2-2x Where 0 < x < 1, the composite negative electrode material is a porous material.
[0023] Titanium and niobium have similar atomic radii and similar chemical properties, while Ti 4+ / Ti 3+ The lithium intercalation / deintercalation plateau corresponding to the redox potential and niobium (Nb) 5+ / Nb 4+ The difference is not significant. The theoretical capacity of the titanium niobium oxide anode (TiNb2O7) is 387.6 mAh / g, and the lattice size before and after lithium insertion / extraction exhibits some expansion and contraction (<10%). Lithium titanate and titanium niobium oxide materials were combined to obtain Li... 4x Ti 4x+1 O 7+5x Nb 2-2x Composite anode materials can utilize the "zero strain" characteristic of lithium titanate to suppress the expansion and contraction of titanium niobium oxide anode materials. The high capacity of titanium niobium oxide anodes leads to a relative increase in energy density. The resulting composite anode material can effectively improve capacity or cycle performance, meeting diverse material requirements. In particular, this application, through the structural design of porous composite anode materials, shortens the diffusion path of lithium ions within the material, thus facilitating electrolyte penetration and improving the battery's rate performance. Overall, a lithium titanate battery with high energy density and high rate performance is achieved. Furthermore, the aforementioned raw materials are inexpensive and readily available, resulting in low cost.
[0024] To further enhance the synergistic effect among the effective components in the composite anode material, thereby obtaining a composite anode material with superior overall electrical performance, the preferred structural formula of the aforementioned composite anode material is xLi4Ti5O. 12 ·(1-x)TiNb2O7, 0<x<1, preferably 0.2≤x≤0.4.
[0025] In one embodiment of this application, the composite negative electrode material is spherical in shape, preferably with a particle size of 10–34 μm and a specific surface area of 9–36 cm². 2 / g.
[0026] The aforementioned composite anode materials with specific particle size and surface area are beneficial for further shortening the diffusion path of lithium ions inside the material and promoting electrolyte wetting, thereby further improving the rate performance of the composite anode materials.
[0027] In another typical embodiment of this application, a method for preparing a composite negative electrode material is provided, the method comprising: step S1, preparing Li4Ti5O 12 Nanoparticles and TiNb2O7 nanoparticles are pelletized to obtain microspheres; in step S2, the microspheres are calcined to obtain a composite anode material.
[0028] By combining lithium titanate and titanium niobium oxide materials, a microsphere composite anode material is obtained. The "zero strain" characteristic of lithium titanate can suppress the expansion and contraction of the titanium niobium oxide anode material, thereby increasing the energy density due to the high capacity of the titanium niobium oxide anode. The resulting composite anode material can effectively improve capacity or cycle performance, meeting diverse material requirements. In particular, this application further enriches the pore structure of the porous composite anode material by calcining the microspheres (the calcination atmosphere can be oxygen, air, nitrogen, or an inert gas), thus shortening the diffusion path of lithium ions within the material and facilitating electrolyte wetting, further improving the battery's rate performance. Overall, a lithium titanate battery with high energy density and high rate performance is obtained. Furthermore, the above preparation method is simple and low-cost.
[0029] To further improve the efficiency of the above calcination and to obtain composite anode materials with rich pore structure as much as possible, the calcination temperature is preferably 500-800℃ and the calcination time is preferably 2-8h.
[0030] In one embodiment of this application, the above-mentioned pelletizing process includes: applying Li4Ti5O 12 Nanoparticles, TiNb2O7 nanoparticles, and a solvent are mixed to obtain a slurry. The slurry is then spray-balled to obtain microspheres. Preferably, the mixing speed is 300–1000 r / min, the mixing time is 1–3 h, the spray-balling temperature is 260–280 °C, the feed rate of the slurry during spray-balling is 1–30 mL / min, the solvent is selected from one or more of water, ethanol, and acetone, the solid content of the slurry is 15–60%, and Li4Ti5O7 is preferred. 12The particle sizes of the nanoparticles and TiNb2O7 nanoparticles are independently 10–300 nm.
[0031] The above-mentioned spray pelletizing method is beneficial for obtaining porous microspheres with rich pores, and the mixing stirring speed is more conducive to obtaining Li4Ti5O. 12 Materials with uniform distribution of nanoparticles and TiNb2O7 nanoparticles in porous microspheres, where spray-forming temperature, feed rate of the mixed slurry, and solid-liquid ratio of the mixed slurry are more conducive to controlling the size and pore structure of the microspheres, are also important. (Li4Ti5O) 12 The particle size of the nanoparticles and TiNb2O7 nanoparticles determines the porosity of the basic structural framework for forming microspheres. The solvent used is one that easily evaporates during spray pelletizing, thus improving the efficiency of spray pelletizing.
[0032] To further improve the uniformity of the mixed slurry, the above mixing preferably includes: Li4Ti5O 12 The nanoparticles are first mixed with a first solvent to obtain a first slurry; the TiNb2O7 nanoparticles are then second mixed with a second solvent to obtain a second slurry; the first and second slurries are then third mixed to obtain a mixed slurry. Preferably, the first and second solvents are each independently selected from one or more of water, ethanol, and acetone; preferably, the solid content of the first and second slurries is each independently 15-60%; preferably, the stirring speeds for the first and second mixing are each independently 1200-1800 r / min; and preferably, the stirring speed for the third mixing is 1500-2400 r / min. The stirring speeds for the first and second mixing are also more conducive to improving the uniformity of the mixed slurry, thereby facilitating the smooth progress of spray pelletizing.
[0033] To improve Li4Ti5O 12 The synergistic effect with TiNb2O7 better integrates the excellent properties of both, resulting in a composite anode material with excellent electrical properties. The aforementioned Li4Ti5O7 is preferred. 12 The molar ratio of TiNb2O7 to TiNb2O7 is 0.2–0.4:0.6–0.8.
[0034] In another typical embodiment of this application, a negative electrode material is provided, which includes a composite material, wherein the composite material is the aforementioned composite negative electrode material.
[0035] The composite anode material of this application, when used as the anode of a battery, enables the corresponding battery to have excellent energy density and rate performance.
[0036] In another typical embodiment of this application, a lithium titanate battery is provided, including a positive electrode and a negative electrode, wherein the negative electrode includes a negative electrode material, which is the negative electrode material described above.
[0037] Lithium titanate batteries containing the above-mentioned negative electrode materials have excellent energy density and rate performance.
[0038] The beneficial effects of this application will be explained below with reference to specific embodiments and comparative examples.
[0039] Example 1
[0040] Take 1 kg of lithium titanate material, use deionized water as a dispersant, mix lithium titanate and dispersant at a weight ratio of 1:5 (stirring speed of 500 r / min), and grind to a first slurry with a particle size D50 of 200-300 nm. The solid content of the first slurry is 16.7%.
[0041] Take 0.5 kg of titanium niobium oxide material, use deionized water as a dispersant, mix lithium titanate and the dispersant in a weight ratio of 1:5 (stirring speed of 500 r / min), and grind to a second slurry with a particle size D50 of 100-200 nm. The solid content of the second slurry is 16.7%.
[0042] The first and second slurries were stirred at 500 r / min (the volume ratio of the first slurry to the second slurry was 1:1) for 2 hours to obtain a third mixing, thus obtaining a mixed slurry.
[0043] The temperature of the spray pelletizing equipment was set at 270℃, and the feed rate of the mixed slurry was controlled at 20mL / min to carry out spray pelletizing and obtain microspheres.
[0044] Microspheres were loaded into a crucible and calcined in an air atmosphere in a sintering furnace. The holding temperature was 550℃ for 2 hours, followed by natural cooling to obtain the composite anode material. The SEM image of this composite anode material is shown below. Figure 1 As shown, Figure 1 A magnified view of a portion of the SEM image, as shown below. Figure 2 As shown, Figure 2 A further magnified view of the SEM image is shown below. Figure 3 As shown.
[0045] Example 2
[0046] The difference between Example 2 and Example 1 is that,
[0047] Li4Ti5O 12 The molar ratio of TiNb2O7 to TiNb2O7 was 0.2:0.8, resulting in a composite anode material.
[0048] Example 3
[0049] The difference between Example 3 and Example 1 is that,
[0050] Li4Ti5O 12 The molar ratio of TiNb2O7 to TiNb2O7 was 0.4:0.6, resulting in a composite anode material.
[0051] Example 4
[0052] The difference between Example 4 and Example 1 is that,
[0053] Li4Ti5O 12 The molar ratio of TiNb2O7 to TiNb2O7 was 0.1:0.9, resulting in a composite anode material.
[0054] Example 5
[0055] The difference between Example 5 and Example 1 is that,
[0056] During calcination, the temperature of the heat preservation zone is 500℃, and the composite anode material is finally obtained.
[0057] Example 6
[0058] The difference between Example 6 and Example 1 is that,
[0059] During calcination, the temperature of the heat preservation zone is 800℃, and the composite anode material is finally obtained.
[0060] Example 7
[0061] The difference between Example 7 and Example 1 is that,
[0062] During calcination, the temperature of the heat preservation zone is 480℃, and the composite anode material is finally obtained.
[0063] Example 8
[0064] The difference between Example 8 and Example 1 is that,
[0065] During calcination, the heat preservation zone time is 8 hours, and the composite anode material is finally obtained.
[0066] Example 9
[0067] The difference between Example 9 and Example 1 is that,
[0068] During calcination, the heat preservation zone time is 5 hours, and the composite anode material is finally obtained.
[0069] Example 10
[0070] The difference between Example 10 and Example 1 is that,
[0071] During calcination, the heat preservation zone time is 1 hour, and the composite anode material is finally obtained.
[0072] Example 11
[0073] The difference between Example 11 and Example 1 is that,
[0074] The stirring speed for the first, second, and third mixing processes was 1000 r / min, and the third mixing time was 1 h, ultimately yielding the composite anode material.
[0075] Example 12
[0076] The difference between Example 12 and Example 1 is that,
[0077] The stirring speed for the first, second, and third mixing processes was 300 r / min, and the third mixing time was 3 h, ultimately yielding a composite anode material.
[0078] Example 13
[0079] The difference between Example 13 and Example 1 is that,
[0080] The stirring speed for the first, second, and third mixtures was 200 r / min, and the composite anode material was finally obtained.
[0081] Example 14
[0082] The difference between Example 14 and Example 1 is that,
[0083] The spray pelletizing temperature is 260℃, and the composite anode material is finally obtained.
[0084] Example 15
[0085] The difference between Example 15 and Example 1 is that,
[0086] The spray pelletizing temperature is 280℃, and the final composite anode material is obtained.
[0087] Example 16
[0088] The difference between Example 16 and Example 1 is that,
[0089] The spray pelletizing temperature is 250℃, and the composite anode material is finally obtained.
[0090] Example 17
[0091] The difference between Example 17 and Example 1 is that,
[0092] During spray pelletizing, the feed rate of the mixed slurry is 1 mL / min, and the composite anode material is finally obtained.
[0093] Example 18
[0094] The difference between Example 18 and Example 1 is that,
[0095] During spray pelletizing, the feed rate of the mixed slurry is 30 mL / min, and the composite anode material is finally obtained.
[0096] Example 19
[0097] The difference between Example 19 and Example 1 is that,
[0098] During spray pelletizing, the feed rate of the mixed slurry was 35 mL / min, and the composite anode material was finally obtained.
[0099] Example 20
[0100] The difference between Example 20 and Example 1 is that,
[0101] The solid content of both the first and second slurries is 15%, ultimately yielding a composite anode material.
[0102] Example 21
[0103] The difference between Example 21 and Example 1 is that,
[0104] Both the first and second slurries have a solid content of 60%, ultimately yielding a composite anode material.
[0105] Example 22
[0106] The difference between Example 22 and Example 1 is that,
[0107] Both the first and second slurries have a solid content of 65%, ultimately yielding a composite anode material.
[0108] Example 23
[0109] The difference between Example 23 and Example 1 is that,
[0110] Li4Ti5O 12 Both the nanoparticles and TiNb2O7 nanoparticles have a particle size of 10–100 nm, resulting in a composite anode material.
[0111] Example 24
[0112] The difference between Example 24 and Example 1 is that,
[0113] Ethanol was used as the dispersant, and the final composite anode material was obtained.
[0114] Comparative Example 1
[0115] The difference between Comparative Example 1 and Example 1 is that the microspheres are not calcined, and the composite anode material is finally obtained.
[0116] Comparative Example 2
[0117] The difference between Comparative Example 2 and Example 1 is that the mixed slurry is not pelletized; instead, it is calcined after the solvent evaporates, and the final composite anode material is obtained.
[0118] Comparative Example 3
[0119] The difference between Comparative Example 3 and Example 1 is that lithium titanate material in the same amount as the total amount of lithium titanate material and titanium niobium oxide material in Example 1 is used alone as the composite anode material.
[0120] Particle size testing method: Approximately 0.15 g of the composite anode materials obtained in Examples 1 to 24 and Comparative Examples 1 to 3 were weighed as samples (with an opacity of approximately 10%). Approximately 4 mL (2 droppers) of a 2% sodium hexametaphosphate solution dispersant was added to each sample, and the mixture was thoroughly mixed. Internal ultrasonic conditions: ultrasonic intensity: 40%, ultrasonic time: 60 s; stirring rate: 2650 r / min. The particle size of each composite anode material was measured, and the final test results are listed in Table 1.
[0121] Specific surface area testing method: BET static nitrogen adsorption method. Approximately 1g of the composite anode materials obtained in Examples 1 to 24 and Comparative Examples 1 to 3 were weighed as samples. The samples were placed in clean BET sample tubes and the moisture was removed by heating in a nitrogen atmosphere. The test process was connected to TriStar3000 software for analysis to obtain the specific surface area of each composite anode material. The final test results are listed in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] Button battery manufacturing method: The composite negative electrode materials obtained in Examples 1 to 24 and Comparative Examples 1 to 3 were prepared into slurries, wherein the mass ratio of the slurry ingredients was any composite negative electrode material: Super P: polyvinylidene fluoride = 90:5:5. The slurry was then coated onto an aluminum foil of a certain size to obtain a lithium titanate negative electrode sheet. Using a lithium sheet as the positive electrode, the batteries were assembled into button batteries and charged and discharged at a rate of 0.1C / 0.1C. During the charging and discharging process, the initial discharge efficiency, capacity, and 100-cycle capacity retention rate of each battery were tested using a Newway or Blue Battery Tester, and the test results are listed in Table 2.
[0126] Table 2
[0127]
[0128]
[0129]
[0130] As can be seen from Tables 1 and 2 above, the calcination of microspheres and the pelletizing treatment of the mixed slurry have a significant impact on the particle size and specific surface area of the final composite anode material, resulting in a large difference in the electrical performance of the corresponding lithium-ion battery. The lithium-ion battery corresponding to the composite anode material obtained in Examples 1 to 24 of this application has excellent first discharge efficiency, capacity and cycle performance.
[0131] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0132] Titanium and niobium have similar atomic radii and similar chemical properties, while Ti 4+ / Ti 3+ The lithium intercalation / deintercalation plateau corresponding to the redox potential and niobium (Nb) 5+ / Nb 4+ The difference is not significant. The theoretical capacity of the titanium niobium oxide anode (TiNb2O7) is 387.6 mAh / g, and the lattice size before and after lithium insertion / extraction exhibits some expansion and contraction (<10%). Lithium titanate and titanium niobium oxide materials were combined to obtain Li... 4x Ti 4x+1 O 7+5x Nb 2-2x Composite anode materials can utilize the "zero strain" characteristic of lithium titanate to suppress the expansion and contraction of titanium niobium oxide anode materials. The high capacity of titanium niobium oxide anodes leads to a relative increase in energy density. The resulting composite anode material can effectively improve capacity or cycle performance, meeting diverse material requirements. In particular, this application, through the structural design of porous composite anode materials, shortens the diffusion path of lithium ions within the material, thus facilitating electrolyte penetration and improving the battery's rate performance. Overall, a lithium titanate battery with high energy density and high rate performance is achieved. Furthermore, the aforementioned raw materials are inexpensive and readily available, resulting in low cost.
[0133] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a composite negative electrode material, characterized in that, The preparation method includes: Step S1, Li4Ti5O 12 Nanoparticles, TiNb2O7 nanoparticles, and a solvent are mixed to obtain a mixed slurry; the mixed slurry is then spray-formed into microspheres. Step S2: The microspheres are calcined at a temperature of 500-800°C for 2-8 hours to obtain the composite anode material. The mixing speed is 300~1000 r / min, and the mixing time is 1~3 h; the spray pelletizing temperature is 260~280℃, and the feed rate of the mixed slurry during spray pelletizing is 1~30 mL / min; the solid content of the mixed slurry is 15~60%. The general structural formula of the composite negative electrode material is Li 4x Ti 4x+1 O 7+5x Nb 2-2x Where 0 < x < 1, the composite negative electrode material is a porous material.
2. The preparation method according to claim 1, characterized in that, In the general formula of the composite negative electrode material, 0.2 ≤ x ≤ 0.
4.
3. The preparation method according to claim 1 or 2, characterized in that, The composite negative electrode material is spherical in shape.
4. The preparation method according to claim 3, characterized in that, The particle size of the composite negative electrode material is 10~34μm.
5. The preparation method according to claim 3, characterized in that, The specific surface area of the composite anode material is 9~36 cm². 2 / g.
6. The preparation method according to claim 1, characterized in that, The solvent is selected from any one or more of water, ethanol, and acetone.
7. The preparation method according to claim 1, characterized in that, The Li4Ti5O 12 The particle size of the nanoparticles and the TiNb2O7 nanoparticles are each independently 10~300 nm.
8. The preparation method according to claim 6, characterized in that, The mixture includes: The Li4Ti5O 12 The nanoparticles are mixed with a first solvent to obtain a first slurry. The TiNb2O7 nanoparticles are mixed with a second solvent to obtain a second slurry. The first slurry and the second slurry are mixed in a third process to obtain the mixed slurry.
9. The preparation method according to claim 8, characterized in that, The first solvent and the second solvent are each independently selected from any one or more of water, ethanol, and acetone.
10. The preparation method according to claim 8, characterized in that, The solid content of the first slurry and the second slurry is independently 15-60%.
11. The preparation method according to claim 8, characterized in that, The stirring speeds of the first mixture and the second mixture are each 1200~1800 r / min independently.
12. The preparation method according to claim 8, characterized in that, The stirring speed for the third mixing step is 1500~2400 r / min.
13. A negative electrode material, said negative electrode material comprising a composite material, characterized in that, The composite material is a composite negative electrode material prepared by the preparation method according to any one of claims 1 to 12.
14. A lithium titanate battery, comprising a positive electrode and a negative electrode, wherein the negative electrode comprises a negative electrode material, characterized in that, The negative electrode material is the negative electrode material according to claim 13.
Citation Information
Patent Citations
Lithium ion battery negative electrode material and preparation method thereof
CN109841830A
Preparation method of lithium battery negative electrode material titanium-niobium composite oxide
CN112103493A
Lithium titanate-modified material and manufacturing method thereof
WO2017197675A1